Unveiling the mediating role of self-esteem in the relationship between physical activity and BMI: A structural equation modeling study in adolescents - Wang, Xuefei; Zhou, Liang (Journal of Asian Scientific Research, 2024)
The purpose of this study was to examine the mediating effect of self-esteem on the relationship between physical activity and Body Mass Index (BMI) in adolescents. Two hundred and sixty-nine adolescents completed the Self-Esteem Scale, the International Physical Activity Questionnaire (IPAQ), and BMI measurements. The Zhengzhou Education Authority facilitated data collection. We used Partial Least Squares (PLS) software for data analysis to evaluate the mediating effect of self-esteem. The results found that physical activity significantly improved self-esteem (β = 0.520, t = 12.881, p <.05) and negatively affected BMI (β = -0.404, t = 7.658, p <.05). The analyses of the Structural Equation Model (SEM) showed that self-esteem demonstrated a significant negative effect on BMI (β=-0.181, t=2.965, p<.05) and mediated the relationship between physical activity and BMI, accounting for 20.6% of the total effect. Thus, elevating adolescents' self-esteem may lead to a direct and indirect reduction in BMI by promoting a heightened inclination towards physical activities. This research indicates that strategies to enhance adolescent health should broaden their focus beyond merely increasing physical activity and include efforts to boost self-esteem. It provides fresh perspectives on the intricacies of adolescent physical health, emphasizing the intricate relationships among physical activity, self-esteem, and BMI.